Mental health disorder among Malaysian universities students during the COVID-19 pandemic / Vikniswari Vija Kumaran ... [et al.] - Kumaran, Vikniswari Vija; Ismail, Mohd Khairi; Thinagar, Sharmila; Roslan, Siti Nurul Munawwarah (Universiti Teknologi MARA, 2022)
In Malaysia, the prevalence of mental diseases has risen dramatically over the last decade. University students tend to be particularly vulnerable to the harmful effects of quarantine when compared to the general population. Indeed, even before the COVID-19 pandemic, young adults' mental health was already a global concern. Young adults (aged 16-24 years) have been demonstrated to be especially vulnerable to mental health difficulties during prior lockdowns. Furthermore, increased public and clinician knowledge of mental health issues has likely resulted in improved reporting and identification of mental disorders. The study aims to evaluate Malaysian students' mental health, particularly from private universities during the COVID-19 pandemic. This study used a quantitative research approach. Descriptive analysis and Exploratory Factor Analysis (EFA) were used to analyze the data collected among university students in Malaysia. The results show that Malaysian university students were facing mental health issues due to high anxiety and depression. Furthermore, results of this study show that high level of depression, anxiety, and stress among Malaysian universities students incurred due to a drastic change in the education system especially in teaching delivery. Overall, this study will contribute to the advancement of research on the mental health and well-being of tertiary education students, particularly in Malaysia for their future growth and further development of the education system.